Development and evaluation of 'Pure Rush': An online serious game for drug education. (6th October 2017) - Stapinski, Lexine A.; Reda, Bill; Newton, Nicola C.; Lawler, Siobhan; Rodriguez, Daniel; Chapman, Catherine; Teesson, Maree
Abstract: Introduction and Aims: Learning is most effective when it is active, enjoyable and incorporates feedback. Past research demonstrates that serious games are prime candidates to utilise these principles, however the potential benefits of this approach for delivering drug education are yet to be examined in Australia, a country where drug education in schools is mandatory. Design and Methods: The serious game 'Pure Rush' was developed across three stages. First, formative consultation was conducted with 115 students (67% male, aged 15–17 years), followed by feasibility and acceptability testing of a prototype of the game ( n = 25, 68% male). In the final stage, 281 students (62% female, aged 13–16 years) were randomly allocated to receive a lesson involving Pure Rush or an active control lesson. The lessons were compared in terms of learning outcomes, lesson engagement and future intentions to use illicit drugs. Results: Students enjoyed playing Pure Rush, found the game age‐appropriate and the information useful to them. Both the Pure Rush and the active control were associated with significant knowledge increase from pre to post‐test. Among females, multi‐level mixed‐effects regression showed knowledge gain was greater in the Pure Rush condition compared to control ( β = 2.36, 95% confidence interval 0.36–4.38). There was no evidence of between condition differences in lesson engagement or future intentions to use illicit drugs. Discussion and Conclusions: Pure Rush is an innovative online drug education game that is well received by students and feasible to implement in schools. [Stapinski LA, Reda B, Newton NC, Lawler S, Rodriguez D, Chapman C, Teesson M. Development and evaluation of 'Pure Rush': An online serious game for drug education. Drug Alcohol Rev 2017]